Real-time feedback improves multi-stakeholder design for complex environmental systems. (26th April 2021) - Guo, Niles; Davis, Alex; Mauter, Meagan; Whitacre, Jay
Abstract: We test whether providing quantitative real-time feedback relating design decisions to system objectives improves group solutions in an interdependent energy-water design task. While prior research suggests an important role of real-time feedback on task performance, few studies have examined the role of real-time feedback in the design of complex environmental systems. We tested a real-time feedback approach using a mixed within- and between-subject experiment (n = 88 Carnegie Mellon University students, divided into 22 groups of four). When compared to individual designs and informal collaborations, real-time performance feedback yielded solutions closer to the Pareto frontier and reduced both financial (by 26% and 21%) and environmental cost (by 34% and 12%). In addition, informal collaboration did not improve group decision-making when compared to individual designs. The results suggest that optimal solutions to meeting energy and water demand while minimizing cost and environmental impact can be obscured in informal collaborations, but that real-time feedback to system designers can help avoid waste of public resources.